Metacognitive Beliefs as a Predictor of Mind Wandering among Taif University Students - Al-Talhi, Noor Ameer; Al-Otaibi, Sameera Mohareb (Journal of Educational and Psychological Sciences, 2025)
The current study aimed at identifying the level of mind wandering and metacognitive beliefs among students at Taif University. It also sought to explore the relationship between mind wandering and metacognitive beliefs. In addition, the predictability of mind-wandering through metacognitive beliefs scale was also targeted. The descriptive (correlational/predictive/comparative) was utilized. The sample comprised (514) students at Taif University. To collect data, mind wandering scale (Erfan, 2022), metacognitive beliefs scale (Wells & Cartwright-Hatton, 2004) that was translated and standardized by (Abdul-Zaher, 2014) were administered. Results showed that mind wandering was moderate among Taif University students, except for the spontaneous mind wandering dimension that was low among the females. Metacognitive beliefs were of moderate level. There was a significant positive relationship between mind wandering and metacognitive beliefs. Metacognitive beliefs was a significant predictor of mind wandering. The most significant predictor was cognitive confidence. Accordingly, the research recommended preparing interventions addressing metacognitive beliefs and reducing mind wandering among university students as they may hinder their academic cognitions.